The Concept of Neuroglia - Verkhratsky, Alexei (Adv Exp Med Biol, 2019)
Neuroglia represent a diverse population of non-neuronal cells in the nervous systems, be that peripheral, central, enteric or autonomic nervous system. Arguably, these cells represent about half of the volume of the human brain. This volumetric ratio, and by extension glia to neurone ratio, not only widely differ depending on the size of the animal species brain and its positioning on the phylogenetic tree, but also vary between the regions of an individual brain. Neuroglia derived from a dual origin (ectoderm and mesodermal) and in an assorted morphology, yet their functional traits can be mainly classified into being keepers of homeostasis (water, ions, neurotransmitters, metabolites, fuels, etc.) and defenders (e.g., against microbial organisms, etc.) of the nervous system. As these capabilities go awry, neuroglia ultimately define their fundamental role in most, if not, all neuropathologies. This concept presented in this chapter serves as a general introduction into the world of neuroglia and subsequent topics covered by this book.